EXTRACTION OF ALKALOIDS AND PROCESSES OCCURRING IN THE BODY - Baykulov Azim Kenjayevich; Toshboyev Feruz Nizomiddinovich; Muratov Muzaffar Shermamatovich (TADQIQOTLAR, 2025)
Annotation:  "Alkaloids"  are  basic  nitrogen-containing  organic  compounds found  in  plants  and  animals.  By  the  19th  century,  strychnine,  quinine,  caffeine, atropine,  ephedrine  and  others  were  isolated  from  alkaloids.  Academicians S.Yu.Yunusov and O.S. Sadikov's work with his students on alkaloids. According to the studies by S.Yu.Yunusov, alkaloids are most abundantly collected from the shoot of the plant in early spring, from the seeds of annual plants in autumn,  from the roots and  seeds  of  perennial  plants.  Chemistry  of  Plant  Substances  of  the  Academy  of Sciences of Uzbekistan in 1943-1993. 266 plant species belongs to 29 families, 345 species were studied at the institute under the leadership of S. Yu. Yunusov, and 913 alkaloids were isolated from them.